2015
DOI: 10.1016/j.jacl.2015.05.002
|View full text |Cite
|
Sign up to set email alerts
|

The risk of cardiovascular events with increased apolipoprotein CIII: A systematic review and meta-analysis

Abstract: The current body of literature includes several methodologically sound studies that together provide consistent evidence for an association of cardiovascular events with blood apoC-III level in total plasma or in VLDL and LDL. More data are needed to determine importance of levels of apoC-III in specific lipoproteins for cardiovascular risk assessment and management and to elucidate the interaction between triglycerides and apoC-III in relation to risk of cardiovascular disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
89
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 113 publications
(92 citation statements)
references
References 48 publications
(161 reference statements)
3
89
0
Order By: Relevance
“…These triglyceriderich lipoproteins carry various atherogenic proteins such as apolipoprotein C-III, itself associated with atherosclerosis and CVD. 93 Replacing 1% of daily energy intake from saturated fat with polyunsaturated or monounsaturated fat lowers triglyceride by 0.9 or 0.4 mg/dL, respectively (Figure 5, left), 4 perhaps more in those with hypertriglyceridemia. 91 Replacing the 1% saturated fat with 1% carbohydrates raises serum triglycerides by ≈1 mg/dL.…”
Section: Triglyceridesmentioning
confidence: 99%
“…These triglyceriderich lipoproteins carry various atherogenic proteins such as apolipoprotein C-III, itself associated with atherosclerosis and CVD. 93 Replacing 1% of daily energy intake from saturated fat with polyunsaturated or monounsaturated fat lowers triglyceride by 0.9 or 0.4 mg/dL, respectively (Figure 5, left), 4 perhaps more in those with hypertriglyceridemia. 91 Replacing the 1% saturated fat with 1% carbohydrates raises serum triglycerides by ≈1 mg/dL.…”
Section: Triglyceridesmentioning
confidence: 99%
“…Elevated plasma TG levels represent a risk factor for CVD in humans, and an adjusted analysis of patients in the Framingham Heart Study suggests that each decrease of 1 mg/dl in plasma ApoC-III levels is associated with a 4% decrease in CVD risk (11), further supporting the potential therapeutic benefit of suppressing plasma ApoC-III levels in humans to reduce CVD. A number of correlative studies showed a greater incidence of CVD in persons with ApoC-III-rich LDL (38). These correlations using ApoC-III associated with LDL are more complex, as it was also reported that increased ApoE content in LDL fractions with ApoC-III is associated with a lower risk of CVD (39).…”
Section: Discussionmentioning
confidence: 99%
“…FCS patients, in particular, have the highest triglyceride levels among patients with hypertriglyceridemia and have frequent episodes of acute pancreatitis, which can be fatal, as well as long-term complications such as pancreatic insuffi ciency and diabetes mellitus ( 25 ). Elevated apoC-III levels and triglycerides are independent risk factors for CVD ( 5,11 ). Recent genetic data has strongly suggested that apoC-III is a causal mediator of CVD ( 12,13 ).…”
Section: Downloaded Frommentioning
confidence: 99%